Optimalisasi Tata Letak : Strategi Untuk Meningkatkan Kepuasan Pelanggan - Khadyra Oktaviani Anwar; Shelsa Debora (Jurnal Manajemen Bisnis Digital Terkini, 2024)
This research conducted aims to explore the important aspects of office layout in a motorcycle dealer company which includes the objectives: (1) Identifying effective office layout strategies in motorcycle dealer companies, (2) Analyzing the effect of office layout on customer satisfaction, (3) Finding ways to optimize customer satisfaction of motorcycle dealer companies through office layout. The type of research is descriptive with a qualitative approach based on the results of direct observation at the Honda Naga Mas Motor Bandung office Jl. Soekarno Hatta No. 529, as well as observing customer reviews on Google regarding the layout of the company. The results showed that Honda Naga Mas Motor Bandung implements an efficient office layout strategy, because the applied office layout can optimize customer satisfaction through positive reviews related to the existing office layout in the company with evidenced of customers who feel more comfortable and easy to get service at the office because of the good office layout. These findings can provide insight and awareness to other motorcycle dealer companies regarding the importance of the right office layout strategy for optimal customer satisfaction.